Coastal Physical Vulnerability of Surabaya and Its Surrounding Area to Sea Level Rise - Sulma, Sayidah; Kusratmoko, Eko; Saraswati, Ratna (UI Scholars Hub, 2012)
The study for coastal vulnerability to sea level rise was carried out in Surabaya and its surrounding area, it has focused on calculations of the physical vulnerability index were used coastal vulnerability index (CVI) methods. It was standardized by the multi criteria analysis (MCA) approach according to the study area. The score of each physical variable derived from remote sensing satellite data and the results of studies that have been done, such as modeling results and thematic maps, and then integrated into geographic information systems (GIS). Result of this study shows that the coastal areas of Gresik, Surabaya, and Sidoarjo in the very low to very high vulnerability level. Physically, the low land areas with open and slightly open coastal have a high vulnerability category. The high level vulnerability was found located in the northern of Madura Strait (Gresik Regency) that overlooks to the Java Sea is about 28.81% from the entire of study areas. Meanwhile, the moderate, low and very low levels of vulnerability were located on Surabaya and Sidoarjo Regency that have more protected coastal area, relatively. According to the physical condition, the coastal elevation is the most variable that contributes to the high of vulnerability index in the coastal of Surabaya City and Sidoarjo Regency.